Application of Titanium Dioxide Nanoparticles Synthesized by Sol-Gel Methods in Wastewater Treatment. (29th August 2021) - Abel, Saka; Jule, Leta Tesfaye; Belay, Fikadu; Shanmugam, R.; Dwarampudi, L. Priyanka; Nagaprasad, N.; Krishnaraj, Ramaswamy
Abstract : Nanotechnology from titanium dioxide has been deposited, and its application in desalination and water treatment has been investigated by using sol-gel methods. Homogeneously dispersed sphere shapes of titanium dioxide nanoparticles were observed from scanning electron microscope micrographs and decrease in size as aging time increases from 40 min to 60 min. SEM micrographs of highly transparent nanopowders show that they are detected in the visible region from UV/visible and that their red shift around maximum wavelength increases with increasing aging time due to an increase in water quality. The energy band gap of the generated nanosheet has narrowed as the aging time has increased, which is related to the red shift of the absorption spectrum edge in the sheet. The structural behaviors of deposited nanoparticles have also been investigated, which confirms the existence of anatase as well as rutile levels in the liquid phase. The findings of the PL allowed us to determine the total strength of the intensity. This shows that applying photodegradation by a solar absorber could play a vital role in desalination and water treatment.